Absence, presence, remembrance: A theological essay on frailty, the university and the city - de Beer, Stephan F. (Verbum et ecclesia, 2013)
This essay is reflecting on frailty, the university and the city, in relation to each other. It seeks to transcend the binary concepts of presence and absence, proposing remembrance as the frail work of making absence present, of reweaving what is dismembered, and of a politics of hospitality. It considers the task of remembrance in the ‘studio of life’, disrupting or transcending the confines of laboratory and asylum.